Peer review of the pesticide risk assessment of the active substance imazamox - European Food Safety Authority (EFSA) (EFSA Journal, 2016)
Abstract The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State France and co‐rapporteur Member State Italy for the pesticide active substance imazamox are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of imazamox as a herbicide on sunflower, alfalfa, oilseed rape and soya bean. The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.